Principal Supervision Management in Enhancing Teachers’ Information and Communication Technology Competence - Lailis Syarofah; Dinny Mardiana (Journal of General Education and Humanities, 2026)
This study aims to explore how principals’ supervision management contributes to improving teachers’ information and communication technology (ICT) competence in elementary schools. Using a qualitative case study design, the research was conducted in two public elementary schools in Tambora District, Jakarta. Data were collected through in-depth interviews, participant observation, and document analysis involving principals, teachers, and school supervisors. The findings reveal that supervision management, implemented through the functions of planning, organising, actuating, and controlling (POAC), plays a strategic role in strengthening teachers’ ICT competence. Participatory planning based on teachers’ needs, collaborative organisation of supervision teams, practice-oriented implementation through coaching and mentoring, and continuous monitoring and evaluation collectively foster teachers’ confidence, creativity, and ability to integrate digital technologies into classroom instruction. This study highlights that effective supervision management goes beyond administrative control and serves as a systemic approach to professional development. The findings have practical implications for school leaders in designing adaptive, sustainable supervision strategies to support digital transformation in elementary education.